APPLICATIONS OF CHITOSAN AND CAFFEINE IN RICEBERRY SEED GERMINATION - Tunma, Somruthai (Life Sciences and Environment Journal, 2017)
This research paper aims to study the effect of chitosan preparation from shrimp shell chitin and the effect of caffeine from coffee grounds on seed germination and seedling growth of riceberry. The experiment was performed with seed soaking 1%, 3% and 5% w/v in caffeine solution and 0.10, 0.30 and 0.50 % w/v in chitosan solution for 7 days. The results showed that all concentration of caffeine solution and 0.10% of chitosan solution stimulated seed germination over the control water-soaked rice whereas application by 0.30% and 0.50% w/v of chitosan solution did not show the effect of seed germination. A study of seedling growth was conducted by sowing seeds in pots and watered with caffeine and chitosan solutions instead of chemical fertilizers and pesticides. When compared to water-soaked rice after 10 days treatment, the results did not show significant differences of a height of seedling growth of riceberry watered with caffeine. However, the seedlings grow 15-30% in height when performed with 3% and 5% w/v of caffeine solution after 30 days of treatment comparing with the control while 0.10 % of chitosan solution showed no significant differences in stimulating root growth and seedling growth when compared to the control. Whereas 0.30 and 0.50 % w/v of chitosan solution did not affect the root growth so it cannot grow when sowing seeds in soil. This study can be further developed in rice organic farming to increase in seed germination and seedling growth.